Strengthening Economic Welfare through Innovative Waqf Management: Insights from Islamic Organizations - Nova Fauzian Ristawati; Makhrus Makhrus (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2025)
This study examines innovations in productive waqf management by nāẓīrs of Islamic community organizations to enhance economic welfare. Using a qualitative field research approach, data were collected through observation, interviews, and documentation of waqf practices in Muhammadiyah and Nahdlatul Ulama in Banyumas. Analysis was conducted through data reduction, presentation, and conclusion drawing to identify management patterns, challenges, and innovation opportunities. Findings highlight the need for digitalization, capacity building, and regulatory reform to optimize productive waqf. Key innovations include the use of digital records to enhance transparency and security in transactions, enabling permanent documentation of fund receipts, investments, and benefit distribution. Integration with the Waqf Information System (SIMSIWAK) facilitates real-time asset monitoring, while smart contracts ensure automatic and targeted fund distribution. However, challenges such as limited digital infrastructure and regulatory gaps persist. Strengthening collaboration between nāẓīrs, Islamic financial institutions, and government bodies is crucial to overcoming these barriers. Digital applications can significantly improve management efficiency, transparency, and community engagement, but building a sustainable waqf ecosystem will require continued investment in infrastructure and regulatory understanding.